2020
DOI: 10.1038/s41598-020-61488-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of acute Rockwood III acromioclavicular dislocations—Comparative study between two flip-button techniques

Abstract: Acromioclavicular joint dislocation is a common shoulder injury, usually caused by direct violence on the shoulder. optimal treatment of type iii is still a hot discussion currently in orthopedic surgeons. With the advent of many flip-button techniques, Tightrope system and Endobutton system become popular techniques for reconstruction of coracoclavicular ligaments. the purpose of the study was to compare the clinical and radiological results between the two techniques. A retrospective casecontrol study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…With careful full‐text reading, 56 studies were excluded for the reasons shown in Figure 1. Finally, 31 articles were included in our study 24–54 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With careful full‐text reading, 56 studies were excluded for the reasons shown in Figure 1. Finally, 31 articles were included in our study 24–54 …”
Section: Resultsmentioning
confidence: 99%
“…Finally, 31 articles were included in our study. 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 …”
Section: Resultsmentioning
confidence: 99%
“…After screening titles/abstracts for satisfying inclusion/exclusion criteria, 177 abstracts were further excluded, leaving 34 unique studies for full-text review. Finally, 14 studies that reported outcomes after the surgical management of acute Rockwood grade III acromioclavicular dislocations were included in this systematic review (Figure 1) [12,19,[26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…However, each of these surgical techniques has complications and the best treatment strategy for CC stabilization remains controversial. The most commonly used surgical procedure is internal fixation with the Endobutton technique, 23 , 24 which can be performed either via open surgery, mini‐open surgery, or arthroscopically. 15 , 16 , 21 Endobuttons technique provide flexible CC stabilization for ACJ dislocation.…”
Section: Discussionmentioning
confidence: 99%